2016
DOI: 10.5433/1679-0359.2016v37n6p4339
|View full text |Cite
|
Sign up to set email alerts
|

Forage intake processes by goats on a massai grass pasture with different sward heights

Abstract: The objective of this study was to evaluate the forage-intake process of goats feeding on Massai grass pastures with different heights (40, 50, 60, and 70 cm). The experimental design was completely randomized, with treatments corresponding to four sward heights with two replicates over time and space. Collected data were related to the forage-intake process and the chemical and morphological composition of the pasture. Grazing trials (45 min) were performed with four Anglo-Nubian crossbred goats. Total forage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Rodrigues et al . (2016) reported that bite rate exhibited a linear and positive correlation with intake. However, the increase of eating time and number of bites could not compensate completely.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodrigues et al . (2016) reported that bite rate exhibited a linear and positive correlation with intake. However, the increase of eating time and number of bites could not compensate completely.…”
Section: Discussionmentioning
confidence: 99%
“…Goats could adjust eating time, bites/step and bite rate to obtain the require intake after the reduction in bite weight. Rodrigues et al (2016) reported that bite rate exhibited a linear and positive correlation with intake. However, the increase of eating time and number of bites could not compensate completely.…”
Section: Goat Eating Behaviourmentioning
confidence: 99%